Effect of Inhomogeneous Broadening in Deep Ultraviolet Light Emitting Diodes - Romer, Friedhard; Witzigmann, Bernd (Proceedings of the International Conference on Numerical Simulation of Optoelectronic Devices, NUSOD, 2021)
Due to their small dimensions deep ultraviolet (DUV) light emitting diodes (LED) are highly attractive light sources for environmental and medical applications. DUV LEDs generate light in active quantum wells (QW) made of Aluminium Gallium Nitride. The QWs are not lattice matched to the substrate and only few monolayers thick making them susceptible to compound fluctuations seen through inhomogeneous broadening (IHB). In this work we analyze by means of self consistent carrier transport and luminescence simulations how the IHB affects the electronic operation and emission polarization of DUV LEDs. We demonstrate that the IHB affects both the internal quantum efficiency and the current versus voltage curve of DUV LEDs.
CRIS-Team Scopus Importer:2021-10-22